The role of artificial intelligence applications in promoting green education for students of Saudi universities (Islamic, Taiba, Tabuk) and the obstacles to their use from their own point of view - Al-Balawi, Asma Hamed; El-Sisi, Areej Hamza (Journal of Educational and Psychological Sciences, 2025)
The study aimed to reveal the role of artificial intelligence applications in promoting green education for students of Saudi universities (Islamic, Taibah, Tabuk) and the obstacles to its use from their point of view. The study used the descriptive survey approach, adopting the questionnaire as a study tool. It was applied to a sample of students at (Islamic University - Taibah University - Tabuk University). The study reached a set of results, the most important of which are: The general arithmetic mean for the first axis reached (4.01) with a relative weight of (80.1%). These values confirm that artificial intelligence applications play a significant role in promoting green education among students in Saudi universities. The general arithmetic mean for the second axis reached (3.34) with a relative weight of (66.7%). These values confirm that there is a medium degree of obstacles to using artificial intelligence to promote green education. The study also showed the presence of a number of obstacles to using artificial intelligence to promote green education among students in Saudi universities at a medium degree. The study recommended spreading awareness among students in universities about the importance of using artificial intelligence applications to promote green education, and planning to include artificial intelligence applications in courses that support the culture of green education.
Keywords: Artificial intelligence; Green education; Saudi universities